Effectiveness of Implementing the Stunting Prevention Program in East Sambirejo Village, Percut Sei Tuan District - Damanik, Ibnu Hajar; Handayani, Silvia Maria; Hasanah, Fadilatul (CV. Rayyan Dwi Bharata, 2025)
Stunting is a condition of failure to thrive in children under five whose height is much shorter than the height of children their age due to malnutrition. Stunting prevention is one of the areas of focus in health development because growth at an early age is an important thing to pay attention to. Because one of the causes of stunting can arise from environmental factors, as well as from the food consumed, whether looking at the source of nutrition or vitamins. The success of the Stunting Prevention Program can be seen if the program's effectiveness refers to measures of program effectiveness. This research aims to analyze the effectiveness of implementing the stunting prevention program in Sambirejo Timur Village, Percut Sei Tuan District. This study used descriptive qualitative method. The subjects in this study were 5 people consisting of the Head of East Sambirejo Village, Village Midwife, Posyandu Cadre, Pregnant Women, Mothers with babies. Data collection uses observation, interview and documentation techniques. Data analysis techniques use data reduction, data presentation and drawing conclusions. Data validity uses source triangulation and technique triangulation. The research results show that the effectiveness of the implementation of the stunting prevention program in the village of East Sambirejo has been said to be effective. This is shown by several programs that have run as expected. The final results of this research conclude that the implementation of the Stunting Prevention Program in East Sambirejo Village, Percut Sei Tuan District has been implemented in accordance with measures of program effectiveness effectively, but is still not optimal. This can be seen from several things, namely in the implementation of socialization there are still people who do not participate in the socialization so there is a lack of human resources who understand the program being implemented.